Literasi Digital: Tingkat dan Keandalan Sumber Referensi Mahasiswa dalam Menulis Esai Akademik - Abdul Haliq; Akmal Hamsa (GERAM: Gerakan Aktif Menulis, 2021)
This study aims to describe the level of digital literacy and the reliability of reference sources for student academic essays. The research uses a quantitative approach with quantitative descriptive research. This research was conducted on 32 students of the UNM Language and Literature Education Study Program which were obtained using purposive sampling technique. Collecting data using questionnaires, documentation, and interviews. The data analysis technique used quantitative descriptive analysis using presentation techniques. The results showed that the digital literacy level of students in general was in the very high category and the reference sources for student academic essays generally came from credible and trusted sources. This means that students have excellent digital literacy skills and are used in learning to write academic essays online by using various technological devices and applications on the internet that support the learning process.